Discovery of inhibitors of protein tyrosine phosphatase 1B contained in a natural products library from Mexican medicinal plants and fungi using a combination of enzymatic and in silico methods** - Díaz-Rojas, Miriam; González-Andrade, Martin; Aguayo-Ortiz, Rodrigo; Rodríguez-Sotres, Rogelio; Pérez-Vásquez, Araceli; Madariaga-Mazón, Abraham; Mata, Rachel (Frontiers in Pharmacology, 2023)
This work aimed to discover protein tyrosine phosphatase 1B inhibitors (PTP1B) from a small molecule library of natural products (NPs) derived from selected Mexican medicinal plants and fungi to find new hits for developing antidiabetic drugs. The products showing similar IC50 values to ursolic acid (positive control, IC50 = 26.5) were considered hits. These compounds were canophyllol (1), 5-O-(β-D-glucopyranosyl)-7-methoxy-3',4'-dihydroxy-4-phenylcoumarin(2), 3,4-dimethoxy-2,5phenanthrenediol (3), masticadienonic acid (4), 4',5,6-trihydroxy-3',7-dimethoxyflavone ( 5), E/Zvermelhotin (6), tajixanthone hydrate (7) quercetin-3-O-(6''-benzoyl)-β-D-galactoside (8), lichexanthone (9), melianodiol (10), and confusarin (11). According to the double-reciprocal plots, triterpenoid 1 was a non-competitive inhibitor, phenanthrene 3 a mixed-type, and 6 competitive. The chemical space analysis of the hits (IC50 < 100 M) and compounds possessing activity (IC50 in the range of 100 to 1000 M) with the BIOFACQUIM library indicated that the active molecules are chemically diverse, covering most of the known Mexican NPs chemical space. Finally, a SAS map was built using the Tanimoto similarity index and the PTP1B absolute inhibitory activity, allowing the identification of seven scaffold hops, namely compounds 3, 5, 6, 7, 8, 9, and 11. Canophyllol (1), on the other hand, is a true analog of UA since it was SAR continuous zone of the SAS map.